Fabrication of graphdiyne and its analogues for photocatalytic application. Issue 3 (9th November 2022) - Liang, Shujie; Deng, Hong; Zhou, Zhi; Wong, Wai‐Yeung
Abstract: Graphdiyne (GDY), an emerging two‐dimensional all‐carbon allotrope, features the coexistence of sp and sp 2 hybridized planar carbon atoms. GDY and GDY‐based materials exhibit unique physical and chemical properties, such as well‐defined molecular skeleton, π‐conjugated structure, high specific surface area with porosity, and good electrical conductivity, which have aroused widespread interest in various disciplines. As an emerging field, in this work, we summarize important synthesis strategies of GDY and GDY‐based materials including classical synthesis, chemical vapor deposition, explosion approach, and interface‐assisted methods. We also elaborate the recent modifications to regulate the structure and properties of GDY from the viewpoint of metal doping, non‐metal doping, and heterostructure construction. Meanwhile, recent achievements and progress in the development of energy and environmental applications in photocatalysis are highlighted. Lastly, the challenges and potential developments of GDY in the catalytic research are given at the end of this article. Abstract : Graphdiyne (GDY) composed of sp 2 and sp carbon atoms has aroused a widespread interest in various fields due to its excellent physicochemical properties. This review systematically summarizes the recent synthetic methods and post‐modifications of GDY and GDY‐based materials for photocatalysis. It also provides a useful guidance for the development of GDY for energy and environmental applications.